PENENTUAN MINAT DAN BAKAT CALON MAHASISWA UNTUK MEMILIH PROGRAM STUDI PADA UNIVERSITAS INDO GLOBAL MANDIRI PALEMBANG DENGANMETODE CASE-BASED REASONING (CBR) - Suryati Suryati; Hastha Sunardi (UNIVERSITAS INDO GLOBAL MANDIRI)
Along with the times in the field of education, with the opening of a new science courses many students are confused to choose college courses. Because prospective students do not know the exact interest and ba tificate. Interest is the tendency of the heart to love something. Talent is a gift / gift given by God since birth .. Sometimes incompatible interests and talents. Talent can affect a person's interest in a case. Sometimes people do not necessarily know that he has the talent sector in the field. The only people interested in these fields, without known whether he was gifted in the same field. To determine the interests and talents of prospective students to choose courses at the University of Indo Global Mandiri Palembang is still left to the students themselves. Interest and aptitude determination system is a Web-based tools for optimizing picture of prospective students in choosing courses according to their interests and talents. The system of determining interest and talent at the University of Indo Global Mandiri Palembang using Case-Base Reasoning (CBR). In the process of CBR outline the process of looking for the highest level of similarity between the old case to answer answer new cases. Semankin high level of similarity, the better the suggested solutions.